Teachers’ Views on the Implementation of Blended Education during the Pandemic in Costa Rica - Elizondo-Mejías, Jonathan (Universidad Estatal a Distancia, 2025)
The pandemic caused by COVID-19 transformed every education system in the world. Nearly a year after the pandemic hit Costa Rica and replaced face-to-face public education with a distance learning model, the Ministry of Public Education decided to implement a blended learning model by 2021, in which students alternate school attendance. The study, conducted in the North-North Regional Education Directorate of Costa Rica, specifically in the cantons of Upala and Guatuso, aimed to represent the views of six primary English teachers on blended education and to deepen the understanding of pedagogical mediation and the work environment during the health crisis. The study was conducted using an inductive qualitative research approach based on a case study design, with data obtained and triangulated from interviews, document collection, and photo elicitation; data analysis was conducted using ATLAS.ti software. Although the theoretical implementation of two combined modalities was initially planned, teachers encountered many modalities due to irregular attendance in face-to-face and virtual classes, poor Internet connectivity, and families' decision not to send their children to school. Educational and school management also played a key role in pedagogical mediation and in the perception of decontextualization and work overload.